2021
DOI: 10.2147/dmso.s274047
|View full text |Cite
|
Sign up to set email alerts
|

A Stronger Association of Epicardial Fat Volume with Non-Valvular Atrial Fibrillation Than Measures of General Obesity in Chinese Patients Undergoing Computed Tomography Coronary Angiography

Abstract: An association of atrial fibrillation (AF) with epicardial fat volume (EFV) varied in different ethnic groups. We evaluated the AF-related risk factors and its association with pericardial fat in Chinese patients. Methods: Patients referred for coronary computed tomography angiography (CCTA) in Shanghai East Hospital during 2012 to 2014 (n=2042, 43.8% women, mean age 65.0 years) had AF and cardiovascular risk assessment. Pericardial fat depots were measured from CT and the association of EFV with non-valvular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, a recent imaging study indicated that valvular heart disease may alter epicardial adipose tissue phenotype in comparison with adipose tissue in non-valvular disease in patients with atrial fibrillation. 51 We assume that severe valvular disease may influence PCAT transcriptome. In that case, we cannot draw definite conclusions for the pathophysiological interpretation of our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent imaging study indicated that valvular heart disease may alter epicardial adipose tissue phenotype in comparison with adipose tissue in non-valvular disease in patients with atrial fibrillation. 51 We assume that severe valvular disease may influence PCAT transcriptome. In that case, we cannot draw definite conclusions for the pathophysiological interpretation of our results.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that epicardial fat thickness (EFT) and epicardial fat volume (EFV), as measured by echocardiography, computed tomography (CT), or magnetic resonance image (MRI), are independent risk factors for the presence and severity of atrial fibrillation [ 3 , 21 , 22 ]. Furthermore, very recent clinical data found that EFT and EFV were significantly associated with AF recurrence after pulmonary vein isolation with at least 1-year follow-up [ 23 ], which was consistent with the findings of a systematic review and meta-analysis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, the associations between eat volume, eat density (Ct attenuation coefficient), and aF or its recurrence have been extensively studied. table 2 summarises the studies searching for associations between eat volume, eat density, and aF, published between January 2020 and March 2022 [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125]. Most of these latter studies found that a higher eat volume, both total-eat volume and La-eat (eat surrounding the left atrium) volume, is associated with a higher prevalence of aF, a higher incidence of postoperative atrial fibrillation (POaF) after coronary artery bypass graft (CaBG), and a higher aF recurrence rate after aF ablation.…”
Section: Eat and Afmentioning
confidence: 99%